Impacto de los servicios turísticos en el desarrollo económico de establecimientos turísticos de la ciudad de Quevedo, año 2021 - Menéndez Olvera, Evelyn Gabriela (2021)
The purpose of this research work is to determine the impact that tourist services generate on the economic development of establishments in the city of Quevedo. For its part, the type of research was descriptive given that the reality of the study was known, where the subject was clearly understood, which served to respond to the objectives set, through the deductive method, the respective conclusions were executed. In the same way, with the help of the observation technique, it was possible to acquire the necessary information so that it was subsequently analyzed. According to the results of the study, there is a deficient interest on the part of the Municipal Government authorities and despite the fact that the city has a large area of natural and cultural resources, the tourist offer is very limited, therefore, some people have chosen to leave. to other tourist destinations which reduces the potential and economic development of the city.